Notes on the becoming-revolutionary and the (micro) political - Pacheco Benites, Alberto (2022)
This article is based on what was stated in a paper that was presented under the same name on the occasion of the fiftieth anniversary of the publication of El Anti-Oedipus. On the one hand, the text seeks to account for some concepts or ideas that are part of the political conceptual corpus that constitutes the work of Félix Guattari and Gilles Deleuze. To do this, in the first section a kind of tour through the bibliography is exposed, highlighting what is core to the interests of what is proposed later. On the other hand –and above all from some scope of Guattari’s work– the text raises the tension and possibilities for political articulations and emergencies, around the production of subjectivity in our context, which is developed throughout of the following paragraphs.